2018
DOI: 10.1002/bio.3516
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ninhydrin reagent for spectrofluorimetric determination of heptaminol in human plasma

Abstract: For the determination of heptaminol (HEP) in its authentic and dosage form as well as in human plasma, a new simple, sensitive and cheap fluorimetric method of analysis was developed and validated. The presented method is based on the reaction between aliphatic primary amino moiety present in HEP with ninhydrin and phenylacetaldehyde using Torell and Stenhagen buffer at pH 8.2 that yields a highly fluorescent derivative which after excitation at 390 nm showed a fluorescence emission at 464 nm. The effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Due to its reproducibility, accuracy, and low cost, ninhydrin is a widely used derivatizing reagent for many primary amine-containing drugs for spectrophotometric and/or spectrofluorimetric analysis. [12][13][14] In this study, ninhydrin was reacted with the primary amine groups in TEIC in the presence of phenylacetaldehyde to produce a fluorogenic product; this product was measured at λ ex 390 nm and λ em 460 nm as excitation and emission wavelengths, respectively, as described in Figure 1(a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its reproducibility, accuracy, and low cost, ninhydrin is a widely used derivatizing reagent for many primary amine-containing drugs for spectrophotometric and/or spectrofluorimetric analysis. [12][13][14] In this study, ninhydrin was reacted with the primary amine groups in TEIC in the presence of phenylacetaldehyde to produce a fluorogenic product; this product was measured at λ ex 390 nm and λ em 460 nm as excitation and emission wavelengths, respectively, as described in Figure 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism and stoichiometry of the reaction between ninhydrin and TEIC were at a ratio of 1:1, as shown in Figure 1(b); this finding agrees with the results from previously reported methods. [12,14]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Various methods have been reported for determining heptaminol in its dosage forms and in plasma. Spectrophotometric [2][3][4] , spectrofluorimetric [4][5][6][7][8] , chromatographic [9][10][11][12][13][14][15][16][17][18][19][20][21][22]] and capillary electrophoretic [23]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] A survey of the relevant literature on midodrine found that it had been quantified in its pharmaceutical preparations or in biological fluids via a variety of analytical approaches that included chromatographic, [6][7][8][9][10][11][12][13][14] spectrophotometric, [15][16][17][18][19] electrochemical [20] and spectrofluorimetric [21] techniques. [1][2][3][4][5] A survey of the relevant literature on midodrine found that it had been quantified in its pharmaceutical preparations or in biological fluids via a variety of analytical approaches that included chromatographic, [6][7][8][9][10][11][12][13][14] spectrophotometric, [15][16][17][18][19] electrochemical [20] and spectrofluorimetric [21] techniques.…”
Section: Introductionmentioning
confidence: 99%